CLINICAL AND TECHNOLOGICAL REHABILITATION OF PARTIAL EDENTATION COMPLICATIONS - Magda-Ecaterina Antohe; Ovidiu Stamatin; Ramona Diana Feier; Monica Andronache; Norina Forna (Romanian Society of Oral Rehabilitation, 2018)
The aim of the study is the quantification of the main factors that influence the rehabilitation of the complications of partially edentation in view of choosing the best therapeutic solution from the field of both classic and modern prostheses, as well as the identification of the clinical and technological rehabilitation actions in agreement with the particularity of the clinical case. Material and Methods: The study lot included a number of 120 patients diagnosed with partially edentation who reported to the Clinical Basis for Education of the Faculty of Dental Medicine in the period 2015-2017, the lot comprising 70 women, 50 men, aged between 38 and 73. The assessment of the patients was made by clinical and paraclinical exams. Results: We notice a prevalence of the female sex, in a proportion of 58.3% of the lot, while the male sex represents 41%, this aspect being influenced more by esthetic reasons, being much stricter in case of the female sex. As far as the status of the local indices is concerned, of course in correlation with the other factors that decisively influence the therapeutic decision, we notice a proportional equality of 50% between the positive and negative clinical - biological indices, a very important aspect in the therapeutic decision to opt for a hybrid prosthesis that uses extra-coronary races as preservation, support and stabilization elements, which can only be used in case of a very good dental implantation. Conclusions: The identification, using clinical and paraclinical methods, of the entire set of complications triggered by edentation is in fact, an essential condition of targeted therapy, but also a starting point for the rigorous selection of the therapeutic algorithm, of the dental materials used and of the requirements related to the recreation of a high-fidelity morphology.